"The interrelationship between interior design elements and architectural rendering" (Comprehensive Journal of Science, 2024)
This research aims to examine the relationship between interior design elements and architectural expression in contemporary architecture by describing the nature of their interconnection within architectural space formation. The study adopts a descriptive approach, focusing on observing phenomena as they exist in reality without analytical or interpretive intervention, and relies on relevant academic sources and literature.The findings indicate that the relationship between interior design and architectural expression is characterized by an integrative nature, where each supports the other within the architectural system, resulting in more coherent spatial environments in terms of both function and aesthetics. The study also reveals a contemporary architectural trend toward reducing the separation between interior and exterior spaces, enhancing spatial and visual continuity within buildings.Overall, the research emphasizes the importance of understanding this relationship as an integrated system that contributes to improving architectural design quality and reflects the evolution of architectural thought toward a more holistic approach to spatial composition.
Keywords: Interior Design, Architectural Expression, Architectural Space, Contemporary Architecture, Design Integration.